2010
DOI: 10.1007/s00436-010-2134-1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and abundance of anisakid nematode larvae in five species of fish from southern Australian waters

Abstract: The aim of the present study was to conduct, in southern Australian waters, a preliminary epidemiological survey of five commercially significant species of fish (yellow-eye mullet, tiger flathead, sand flathead, pilchard and king fish) for infections with anisakid nematodes larvae using a combined morphological-molecular approach. With the exception of king fish, which was farmed and fed commercial pellets, all other species were infected with at least one species of anisakid nematode, with each individual ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 29 publications
2
24
1
Order By: Relevance
“…Although little is known about the ecology and epidemiology of anisakid nematodes in Australia [16,17,[29][30][31][32][33], a recent preliminary epidemiological survey of five commercially significant species of fish in southern Australian waters showed that four were infected with at least one of five anisakids (Anisakis, Contracaecum types I and II and Hysterothylacium types IV and VIII) [16]. In another report, Shamsi [34] described eight new types of Hysterothylacium from 20 fish species (n 5 81) collected from different parts of Australia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although little is known about the ecology and epidemiology of anisakid nematodes in Australia [16,17,[29][30][31][32][33], a recent preliminary epidemiological survey of five commercially significant species of fish in southern Australian waters showed that four were infected with at least one of five anisakids (Anisakis, Contracaecum types I and II and Hysterothylacium types IV and VIII) [16]. In another report, Shamsi [34] described eight new types of Hysterothylacium from 20 fish species (n 5 81) collected from different parts of Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Using suitable genetic markers, electrophoretic and sequencing methods can overcome this limitation [15]. A number of studies have demonstrated that the first and second internal transcribed spacers (ITS-1 and ITS-2, respectively) of nuclear ribosomal DNA (rDNA) provide suitable genetic markers for the identification of anisakid species, irrespective of developmental stage [16][17][18][19][20][21][22][23][24][25][26][27], and PCR-coupled mutation scanning of the ITS-1 and/or ITS-2 combined with targeted sequencing [28] provides a powerful approach for exploring the genetic composition of anisakid populations and for investigating their biology.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of larval stages of Anisakid nematodes in fish is a problem for commercial fishing industries due to the potential risk of transmission of zoonotic diseases such as anisakiasis (6)(7)(8), and foodborne allergenicity (9,10). Currently, fish diseases, in particular those caused by parasites, constitute one of the most important problems and challenges confronting fish farming (11).…”
Section: Introductionmentioning
confidence: 99%
“…Although larval stages are found commonly in species of teleosts, frequently in species used for human consumption, identification beyond the level of genus is virtually impossible using morphological methods, resulting in the larvae being assigned to various morphotypes designated by Roman numerals (Cannon 1977a(Cannon , 1977bCannon 1989, 1990;Bruce 1990aBruce , 1990bNash 1998;Lymbery et al 2002;Doupé et al 2003;Muñoz et al 2007;Shamsi 2007;Shamsi et al 2008Shamsi et al , 2011aShamsi et al , 2011bShamsi et al , 2012Jabbar et al 2012aJabbar et al , 2012b. The more recent introduction of molecular techniques has allowed the identification of some larval stages in teleosts and, as a consequence, the identification of life-cycle patterns Nascetti 2006, 2008).…”
Section: Introductionmentioning
confidence: 99%